Endogenous Aspergillus endophthalmitis in a healthy individual - Manandhar, A; Bajracharya, L (Nepalese Journal of Ophthalmology, 2012)
Background: Fungal endogenous endophthalmitis in a healthy individual without any predisposing factors is very uncommon. It can occur in intravenous drug abusers, where Aspergillus is more frequently isolated as the causative organism. Case: We treated an unusual case of culture-proven endogenous Aspergillus endophthalmitis who was immunocompetent and was not an intravenous drug user. The affected eye was successfully treated with repeated intravitreal, intracameral and intrastromal injections of amphotericin B and anterior chamber wash. Conclusion: Endogenous fungal endophthalmitis can occur in healthy individuals. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5873 NEPJOPH 2012; 4(1): 179-183